Healthy Aging—Nutrition Matters: Start Early and Screen Often. Issue 4 (10th April 2021) - Roberts, Susan B; Silver, Rachel E; Das, Sai Krupa; Fielding, Roger A; Gilhooly, Cheryl H; Jacques, Paul F; Kelly, Jennifer M; Mason, Joel B; McKeown, Nicola M; Reardon, Meaghan A; Rowan, Sheldon; Saltzman, Edward; et al.
ABSTRACT: The amount of time spent in poor health at the end of life is increasing. This narrative review summarizes consistent evidence indicating that healthy dietary patterns and maintenance of a healthy weight in the years leading to old age are associated with broad prevention of all the archetypal diseases and impairments associated with aging including: noncommunicable diseases, sarcopenia, cognitive decline and dementia, osteoporosis, age-related macular degeneration, diabetic retinopathy, hearing loss, obstructive sleep apnea, urinary incontinence, and constipation. In addition, randomized clinical trials show that disease-specific nutrition interventions can attenuate progression—and in some cases effectively treat—many established aging-associated conditions. However, middle-aged and older adults are vulnerable to unhealthy dietary patterns, and typically consume diets with inadequate servings of healthy food groups and essential nutrients, along with an abundance of energy-dense but nutrient-weak foods that contribute to obesity. However, based on menu examples, diets that are nutrient-dense, plant-based, and with a moderately low glycemic load are better equipped to meet the nutritional needs of many older adults than current recommendations in US Dietary Guidelines. These summary findings indicate that healthy nutrition is more important for healthy aging than generally recognized. Improved public health messaging about nutrition and aging, combined with routine screening and medical referrals for age-related conditions that can be treated with a nutrition prescription, should form core components of a national nutrition roadmap to reduce the epidemic of unhealthy aging. Abstract : Healthy nutrition has a broad, underrecognized role in preventing aging-related diseases and conditions. Updated public health recommendations on nutrition are needed to support healthy aging.